Designing Project-Based Narrative Text Using Wattpad - Elvyra Elvyra; Leil Badrah Zaki (ConCEPt - Conference on Community Engagement Project, 2024)
Today's teaching is not the same as the one that people did several decades ago. Several decades ago, people used blackboards and textbooks in the classroom. But nowadays, people use digital technologies in teaching and learning activities. This study aims to develop project-based learning for Narrative text by using Wattpad. This research uses Research and Development (RnD) method. The first step is collecting data through questionnaire and interview. The result showed that students had high expectations towards ICT use in English Language Learning, where 42,4% of students hoped that digital-based learning media would be used more often in the learning process. Thus, the author will design teaching material and assessments that is integrated with ICT (Information and Communication Technology). During the progress of making the output, the author will consult with the lecturer to design a more optimal and effective output. The output will be implemented in the partner school on the second week of January 2023.